THE ROLE OF VLOGS INTEGRATION ENHANCING ENGLISH LANGUAGE SKILLS: A SYSTEMATIC LITERATURE REVIEW - Nina Isnaiyah, Respi Apriliandini, Nafan Tarihoran (Integrative Perspectives of Social and Science Journal, 2025)
In the digital era, technology plays a vital role in education, including the learning of the English language. Video blogs (vlogs) have become an innovative tool for enhancing English language skills, particularly in speaking, writing, listening, and vocabulary enrichment. This study employs the Systematic Literature Review (SLR) method using the PRISMA framework (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Articles were collected from academic databases, including ResearchGate (7), Taylor & Francis (6), and ScienceDirect (7). Relevant articles were selected through identification, screening, and eligibility assessment based on inclusion and exclusion criteria. Out of 145 identified articles, 20 were selected for analysis. The results indicate that integrating vlogs into English language learning offers various benefits, including improved speaking fluency, pronunciation, and students’ confidence. Additionally, vlogs support writing skill development through multimodal composition, fostering creativity and student engagement. However, some challenges were identified, including technical difficulties, a lack of experience in video editing, and varying levels of digital literacy. Vlogs have proven to be an effective learning tool for improving students' English language skills and digital literacy. Despite technical challenges, vlogs provide a more interactive and authentic learning experience compared to conventional methods. This study recommends further research on optimizing vlog-based learning strategies, with a focus on developing technical solutions and providing structured guidance for both students and educators.